2020
DOI: 10.1021/jacs.0c07300
|View full text |Cite
|
Sign up to set email alerts
|

Two-State Reactivity in Iron-Catalyzed Alkene Isomerization Confers σ-Base Resistance

Abstract: A low-coordinate, high spin (S = 3/2) organometallic iron­(I) complex is a catalyst for the isomerization of alkenes. A combination of experimental and computational mechanistic studies supports a mechanism in which alkene isomerization occurs by the allyl mechanism. Importantly, while substrate binding occurs on the S = 3/2 surface, oxidative addition to an η1-allyl intermediate only occurs on the S = 1/2 surface. Since this spin state change is only possible when the alkene substrate is bound, the catalyst h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 84 publications
6
54
0
1
Order By: Relevance
“…We suggest that the doublet spin state of the complex is largely preserved throughout the catalytic cycle, although we have also investigated the other spin states, with a particular focus on the trans ‐selective route. While the quartet 1 B was calculated to be more stable than the doublet by 21.0 kcal mol −1 , we found, similarly to Smith, [13] that the activation barrier for the trans selective oxidative addition on the quartet surface (Δ G ≠ =45.0 kcal mol −1 ) was far in excess of what might be considered accessible under the experimental conditions used (see Supporting Information). In addition to this, our EPR results do not support the presence of a quartet Fe I species, or a quartet Fe III species.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…We suggest that the doublet spin state of the complex is largely preserved throughout the catalytic cycle, although we have also investigated the other spin states, with a particular focus on the trans ‐selective route. While the quartet 1 B was calculated to be more stable than the doublet by 21.0 kcal mol −1 , we found, similarly to Smith, [13] that the activation barrier for the trans selective oxidative addition on the quartet surface (Δ G ≠ =45.0 kcal mol −1 ) was far in excess of what might be considered accessible under the experimental conditions used (see Supporting Information). In addition to this, our EPR results do not support the presence of a quartet Fe I species, or a quartet Fe III species.…”
Section: Resultssupporting
confidence: 79%
“…Mechanistic studies revealed that the reaction is likely to proceed via an iron‐hydride with subsequent olefin insertion and β‐hydride elimination [12] . Pertinent to this study, Smith has employed an Fe I species, exploiting the propensity for spin crossover, to achieve iron catalyzed double bond isomerization via a two‐electron catalytic cycle [13] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these results, together, point to a π–allyl (1,3–hydrogen shift) rather than a σ–alkyl (1,2–hydrogen shift) mechanism (Supplementary Fig. 20 ) 48 . Figure 6 shows the plausible mechanism for the Ru–catalyzed alkene isomerization reaction reported here.…”
Section: Resultsmentioning
confidence: 83%
“…This process involves a square‐planar transition state which requires crossing to the lower energy paramagnetic surface(s) at this geometry, introducing small paramagnetic contributions. The involvement of different spin‐surfaces during the geometric interconversion is akin to “two‐state reactivity”, which has been extensively studied computationally to explain the reactivity of high‐valent iron‐oxo complexes [37–39] and organometallic iron compounds [40–42] …”
Section: Resultsmentioning
confidence: 99%